Ovine footrot: new insights into bacterial colonisation - Maboni, G.; Frosth, S.; Aspán, A.; Tötemeyer, Sabine (BMJ Publishing Group, 2016)
Ovine footrot is characterised by interdigital dermatitis (ID) and by the separation of the skin and hoof horn (under-running footrot). Dichelobacter nodosus is the essential pathogen causing footrot; the role of other microorganisms in this disease remains unclear. The aims of this study were (i) to investigate the colonisation of D nodosus, Fusobacterium necrophorum and Treponema species in biopsies from the ovine interdigital skin of healthy, ID and footrot-affected feet and (ii) to characterise the virulence of D nodosus strains in those biopsies. Postslaughter biopsy samples (n=241) were collected and analysed by real-time PCR to determine prevalence and load of the different bacterial species. The highest prevalence and load of D nodosus were found on feet with ID. The vast majority of samples contained virulent D nodosus and some samples contained both virulent and benign D nodosus. Notably, the more pathogenic subspecies of F necrophorum was found in samples from UK sheep. Our findings provide further insights into the role bacterial colonisation may play in the early stage of ID and in the progression towards footrot.